2017
DOI: 10.3389/fphys.2017.00437
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Abdominal Fetal Electrocardiography in Early Intrauterine Growth Restriction

Abstract: Objectives: This descriptive study was performed to evaluate the capability of a non-invasive transabdominal electrocardiographic system to extract clear fetal electrocardiographic (FECG) measurements from intrauterine growth restricted (IUGR) fetuses and to assess whether abdominal FECG parameters can be developed as markers for evaluating the fetal cardiac status in IUGR.Methods: Transabdominal FECG was attempted in 20 controls and 15 IUGR singleton pregnancies at 20+0−33+6 weeks gestation. Standard ECG para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 28 publications
2
17
0
3
Order By: Relevance
“…The other records that were used for validation were DUS and fsECG. In DUS records, end of T waves is equivalent to the Ac as mentioned in several literature [2,[23][24][25][26][27]. In this study, the time duration in which an Ac point was identified between two R peaks was approximately 170 ms-330 ms from an R peak.…”
Section: Validation Of the Model-based Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…The other records that were used for validation were DUS and fsECG. In DUS records, end of T waves is equivalent to the Ac as mentioned in several literature [2,[23][24][25][26][27]. In this study, the time duration in which an Ac point was identified between two R peaks was approximately 170 ms-330 ms from an R peak.…”
Section: Validation Of the Model-based Resultssupporting
confidence: 57%
“…C. Velayo el al. [2] report fHR, QT and QTc values of (149 ± 9) bpm, (234 ± 23) ms and (370 ± 40) ms, respectively, for 20 healthy fetuses (GA: 20-33 weeks). C. Velayo el al.…”
Section: Plos Onementioning
confidence: 99%
See 3 more Smart Citations